Longitudinal associations between social anxiety symptoms and cannabis use throughout adolescence: the role of peer involvement - Nelemans, Stefanie A. (Eur Child Adolesc Psychiatry, 2015)
There appear to be contradicting theories and empirical findings on the association between adolescent Social Anxiety Disorder (SAD) symptoms and cannabis use, suggesting potential risk as well as protective pathways. The aim of this six-year longitudinal study was to further examine associations between SAD symptoms and cannabis use over time in adolescents from the general population, specifically focusing on the potential role that adolescents’ involvement with their peers may have in these associations. Participants were 497 Dutch adolescents (57 % boys; M(age) = 13.03 at T(1)), who completed annual self-report questionnaires for 6 successive years. Cross-lagged panel analysis suggested that adolescent SAD symptoms were associated with less peer involvement 1 year later. Less adolescent peer involvement was in turn associated with lower probabilities of cannabis use as well as lower frequency of cannabis use 1 year later. Most importantly, results suggested significant longitudinal indirect paths from adolescent SAD symptoms to cannabis use via adolescents’ peer involvement. Overall, these results provide support for a protective function of SAD symptoms in association with cannabis use in adolescents from the general population. This association is partially explained by less peer involvement (suggesting increased social isolation) for those adolescents with higher levels of SAD symptoms. Future research should aim to gain more insight into the exact nature of the relationship between anxiety and cannabis use in adolescents from the general population, especially regarding potential risk and protective processes that may explain this relationship.